Hipertensi Emergency - Irwandi Irwandi; Jihan Haura (Jurnal Ilmiah Kedokteran dan Kesehatan, 2023)
Hypertension emergency is defined as a severe increase in blood pressure that is > 180/120 mmHg and there is evidence of worsening or target organ damage. The heart, brain and kidneys are the intended target. In this situation, immediate action to reduce blood pressure is needed within minutes. Risk factors that need to be considered in hypertensive crisis patients are those who are not diagnosed or do not adhere to treatment. Handling this can be done by adhering to medication and diligently taking medications that have been recommended by the doctor.